Trileucine residues in a ligand-CPP-based siRNA delivery platform improve endosomal escape of siRNA. (21st April 2017) - Ullah, Irfan; Chung, Kunho; Beloor, Jagadish; Kim, Jongkil; Cho, Minyoung; Kim, Nahyun; Lee, Kuen Yong; Kumar, Priti; Lee, Sang-Kyung
Abstract: siRNA entrapment within endosomes is a significant problem encountered with siRNA delivery platforms that co-opt receptor-mediated entry pathways. Attachment of a cell-penetrating peptide (CPP), such as nona-arginine (9R) to a cell receptor-binding ligand like the Rabies virus glycoprotein, RVG, allows effective siRNA delivery to the cytoplasm by non-endocytic pathways, but a significant amount of siRNA complexes also enters the cell by ligand-induced receptor endocytosis and remain localized in endosomes. Here, we report that the incorporation of trileucine (3 Leu) residues as an endo-osmolytic moiety in the peptide improves endosomal escape and intracellular delivery of siRNA. The trileucine motif did not affect early non-endosomal mechanism of cytoplasmic siRNA delivery but enhanced target gene silencing by >20% only beyond 24 h of transfection when siRNA delivery is mostly through the endocytic route and siRNA trapped in the endosomes at later stages were subject to release into cytoplasm. The mechanism may involve endosomal membrane disruption as trileucine residues lysed RBCs selectively under endosomal pH conditions. Interestingly <3 Leu or >3 Leu residues were not as effective, suggesting that 3 Leu residues are useful for enhancing cytoplasmic delivery of siRNA routed through endosomes.